The Role of Alternative Dispute Resolution Institutions in the Financial Services Sector in Resolving Insurance Disputes - Arista, Tia; Wardhani, Novea Elysa; Evi, Evi (Journal of Law, Politic and Humanities, 2025)
The Alternative Dispute Resolution Institution in the Financial Services Sector (LAPS-SJK) is an institution that facilitates dispute resolution through non-litigation channels with the principles of justice and efficiency. The purpose of this study is to determine how to resolve insurance disputes through Mediation and Arbitration services at LAPS-SJK such as the Regulations and Procedural Process briefly. This study uses a normative legal research method with qualitative data analysis techniques, then the results of the study are presented in a scientific paper that describes the role and mechanism of LAPS-SJK in resolving insurance disputes. The research results show that although LAPS-SJK aims to provide affordable fees, until now there has been no transparency regarding the fee structure charged for various types of disputes which can be an obstacle for less fortunate parties. This study also shows that dispute resolution through Mediation and Arbitration can be an effective solution to reduce insurance disputes in Indonesia. It is important to increase socialization regarding this mechanism so that more parties use the existing alternative dispute resolution